MODELS OF AGRARIAN REFORMS IN CIS COUNTRIES - Svetlana V. Ivanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article shows variable market reforms of the agrarian sphere in CIS countries. In particular, the author characterizes Russian, Belorussian, Armenian and Asian models of transfer from socialism to capitalist relations in rural areas. A clear indicator of agriculture restructuring results is changing the figure of animal produce consumption per capita in CIS countries before and after reforms. The most advanced in the integration aspect part of CIS space is the Eurasian Economic Union, which includes Armenia, Belorussia, Kazakhstan, Kirgizia and Russia. The author summarizes indictors of the mentioned countries dependence on import of certain food stuffs.